THE DEVELOPMENT OF LINEAR MULTIMEDIA IN TEACHING OPENING-CLOSING SKILL AND GIVING REINFORCEMENT SKILL IN MICROTEACHING CLASS AT ENGLISH EDUCATION DEPARTMENT - ., Putu Chintya Dewi; ., I G A Lokita P Utami, S.Pd.; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Desain penelitian dari abstrak ini bertujuan untuk meneliti dan mengembangkan multimedia linear dalam mengajarkan keterampilan membuka-menutup pelajaran dan keterampilan memberikan penguatan. Penelitian ini terdiri dari beberapa tahap; a) penelitian dan pengumpulan data, b) perencanaan, c) pembuatan prototipe d) penilaian awal produk, dan e) peningkatan produk. Instrument daripada penelitian ini adalah kuisioner penilaian ahli dan kuisioner penilaian pengguna. Semua data dianalisis secara kualitatif dan kuantitatif. Hasil dari penelitian ini berupa multimedia linear yakni dalam bentuk video dimana Bahasa Inggris sebagai mata pelajaran dan bahasa pengantar dalam video dan menggunakan murid SMP sebagai model murid di simulasi. Isi daripada video microteaching dikembangkan berdasarkan analisis kebutuhan dari mahasiswa Jurusan Pendidikan Bahasa Inggris. Lebih lanjut, multimedia linear dalam mengajar keterampilan membuka-menutup pelajaran dan keterampilan memberikan penguatan ini dikembangkan dengan mempertimbangkan indicator keberhasilan oleh Tegeh and Kirna (2010). Berdasarkan hasil dari penilaian ahli dan pengguna, kualitas linear multimedia ini sangat bagus.Kata Kunci : Keterampilan Membuka-Menutup Pelajaran, Keterampilan Memberikan Penguatan, Keterampilan Microteaching, Multimedia Linear, Video This resreach and development research design was aimed at studying and developing linear multimedia in teaching opening-closing skill and giving reinforcement skill. This research consisted of six phases: a) research and data collection, b) planning, c) creating product d) product testing, e) evaluating result of product testing, and f) upgrading product. The instrument of this research was expert judgment form and user form. All data were both analyzed descriptively and quantitatively. The result of this research was a linear multimedia which is video that contains English as subject material in teaching the microteaching skills, use English as the language instruction and use Junior High School students as the model in the simulation. The content of the microteaching video was developed based on the need analysis of English Education Department Students. Furthermore, linear multimedia in teaching opening-closing skill and giving reinforcement skill was developed by considering the indicator of success from Tegeh (2010). Based on the result of experts’ judgment and users, the quality of linear multimedia was excellent. keyword : Giving Reinforcement Skill, Linear multimedia, Microteaching Skill, Video, Opening-Closing skill